2010
DOI: 10.1111/j.1365-2133.2010.09941.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality in patients with severe psoriasis: a population-based cohort study in the U.K.

Abstract: Background-Severe psoriasis is associated with excess mortality and increased risk of cardiovascular death. Population-based data evaluating cause-specific mortality in patients with psoriasis are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
338
1
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(379 citation statements)
references
References 54 publications
10
338
1
15
Order By: Relevance
“…In addition, approximately 31% of the PsA patients reported having an infection that required treatment with an antibiotic. A recent study from the UK demonstrated that infection was an important cause of death among patients with severe psoriasis (35). Whether this is related to the inflammatory process or to immunosuppression from medications is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, approximately 31% of the PsA patients reported having an infection that required treatment with an antibiotic. A recent study from the UK demonstrated that infection was an important cause of death among patients with severe psoriasis (35). Whether this is related to the inflammatory process or to immunosuppression from medications is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [40][41][42] showed an increased cancer-related mortality in psoriasis inpatients 41,42 or in patients with severe psoriasis. 40 These populations are highly selected and it is difficult to extrapolate the results to the entire psoriasis patient population. There is no robust evidence to state that cancer mortality is higher in psoriasis patients than in the general population.…”
Section: Cancersmentioning
confidence: 99%
“…The absolute and excess risk of death was highest for cardiovascular disease (61.9 and 3.5 deaths per 1000 patient-years, respectively). Severe psoriasis is associated with an increased risk of death from a variety of causes, with cardiovascular death being the most common aetiology (Abuabara et al, 2010).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The authors also compared CV risks in patients with severe psoriasis with the risks in patients with diabetes mellitus and found comparable increases in major adverse CV events and CV deaths in these groups, demonstrating the clinical importance of the risk of CV disease attributable to psoriasis. Other recent studies have investigated the clinical significance of CV risk in patients with severe psoriasis, demonstrating that these patients have about a 6-year reduction in life expectancy and that excess risk of CV death is the largest contributor to this premature mortality (Abuabara et al, 2010;Gelfand et al, 2011) …”
Section: Cardiovascular Diseasementioning
confidence: 99%